Charge trapping in SiO2 substrate during electron beam deposition of CaF2 thin films of different thicknesses - Marina Romanova; Sergii Chertopalov; Yuri Dekhtyar; Ladislav Fekete; Ján Lančok; Michal Novotný; Petr Pokorný; Anatoli I. Popov; Hermanis Sorokins; Aleksandr Vilken (Optical Materials: X)
The charge trapping phenomenon in the SiO2 layer of Si/SiO2 substrates during the electron beam deposition of CaF2 thin films of varying thicknesses (50–277 nm) was studied. Photoelectron emission (PE) spectroscopy was employed to analyze electron trapping mechanisms induced by the deposition process. Distinct peaks corresponding to electron traps in the SiO2 layer were identified in the PE spectra of CaF2 films. The intensity of these peaks varied with the film thickness and the accumulated electron irradiation dose. The study also investigated the relaxation of the PE spectra in both vacuum and air environments. In a vacuum, the PE peaks and integrated PE intensity remained stable for at least 24 h for CaF2 films of all thicknesses. When exposed to air, the PE peaks persisted for several days in films 125 nm thick or thinner but relaxed within several hours in 277 nm films. This rapid relaxation was attributed to a relatively high irradiation dose (about 2.5 mC) obtained during the fabrication of the 277 nm film, leading to an increased concentration of ionized F centers at the SiO2–CaF2 interface and the formation of (O2–-VA) centers upon air exposure. The relaxation of the PE spectrum intensity was attributed to electron transfer from SiO2 traps to (O2–-VA) centers. Furthermore, the possibility of a 260 nm electron escape depth for CaF2 material was confirmed.